Sex differences in aggression: The role of inhibitory control - DRISCOLL, HELEN,PATRICIA (2011)
Women engage in far less direct aggression and crime than men. Given the potential rewards of aggression, women’s desistance requires explanation. This thesis examined Campbell’s (2006) proposal that sex differences in aggression are mediated by women’s greater fear and inhibitory control. Campbell (1999) argued that women are more fearful of activities associated with risk of physical harm due to high fitness costs incurred by offspring as a result of maternal death or injury in the ancestral environment. In a large adolescent sample (Chapter 3), harm avoidance emerged as the primary mediator of sex differences, though inhibitory control was a significant partial mediator. Campbell’s theory has been extended to explaining sex differences in experiences of aggression (‘social representations’). Women’s more expressive experience (as a loss of control) may represent an accurate ‘readout’ of their experience, whereby superior inhibitory control of anger results in behavioural expression at a higher level of arousal. Chapter 2 reports the results of a confirmatory factor analysis, which confirmed the superior psychometric status of the Revised Short Expagg (which measures the experience of aggression); This measure was incorporated into the study reported in Chapter 3. Women’s lesser aggression was also explained by their relatively more expressive representation, providing support for the ‘readout’ theory. Research which has established sex symmetry in partner-directed aggression (Chapter 4) presented a critical test of Campbell’s theory. It was proposed that women experience a reduction in fear and inhibitory control in intimate relationships. To test this, a context-specific measure of inhibition was developed (Chapter 5). Women from community samples reported significantly less inhibition than men on this measure (Chapters 5 & 6). In the study reported in Chapter 6, women’s perpetration of partner aggression was associated with lower inhibition on one measured domain (the tendency to express honest appraisals rather than engage in tactful dishonesty). Women’s aggression was associated with an instrumental experience, indicative of control motives. However, fear was positively associated with aggression perpetration, though it was unclear whether fear was a precursor to, or a consequence of aggression. Implications for avoidant and appetitive theories of sex differences are discussed in Chapter 7